Prevalence and risk factors of Apical periodontitis in endodontically treated teeth: cross-sectional study in an Adult Moroccan subpopulation - Imane El Ouarti; Sanaa Chala; Majid Sakout; Faiza Abdallaoui (BMC, 2021)
Abstract Background The present study aimed at investigating the prevalence of Apical periodontitis in a Moroccan Adult subpopulation with a non-surgical root canal treatment and to assess associated risk factors including endodontic treatment quality, periodontal health status, coronal restoration cavity design and quality. Methods A total of 358 endodontically treated teeth were evaluated after more than 1-year period in a Moroccan subpopulation according to predetermined criteria. Studied parameters were assessed clinically and radiographically. The association between coronal restoration quality, cavity design, periodontal status, root canal filling quality, coronal restoration related features, presence or absence of the opposing dentition and the periapical status was determined. Data were analyzed using chi-square test, odds ratio and logistic regression. Results The present study revealed that gingival health, coronal restoration with CL II cavity design, and root canal filling quality influenced periapical status of endodontically treated teeth. Multivariate analysis showed that this association was statistically significant for gingival inflammation (95% CI 1.08-3.91, OR 2.05, p = 0.02), inadequate coronal restoration (95% CI 1.16-4.04, OR 2.16, p = 0.01), inadequate root canal filling length and homogeneity (95% CI 1.24-3.01, OR 1.93, P = 0.004), (95% CI 1.41-4.44, OR 2.50, p = 0.002) respectively. Conclusions The present study revealed that inadequate coronal restorations especially with large proximal margins (CL II cavity design) and gingival inflammation increased the risk of apical periodontitis in endodontically treated teeth. Prevalence of Apical periodontitis in the present study was 72.1%.